Rethinking Black Rage in and with James Cone’s Black Theology and Black Power - Xavier Pickett (Religions, 2025)
By exploring how Cone employs and emulates Black literary sources, this article argues that his theological writing can be understood as often translating and thereby making explicit the significance of the inner, emotional lives of Black folks, particularly Black rage, into Black theological thought. The argument, in other words, is that Cone’s writing is an ethical performance of rage and a literary process of reforming his rage. His performance of rage is ethical in that it is morally motivated by injustice and indifference. It is not a performance for its own sake or to simply blow off steam. The performance takes a literary form and becomes the means through which his rage is reformed. The aim of this article demonstrates how his theological writing copes with and transforms rage into ethical discourse.